Alternative expression of TCRζ related genes in patients with chronic myeloid leukemia - Zha Xianfeng; Yan Xiaojuan; Shen Qi; Zhang Yuping; Wu Xiuli; Chen Shaohua; Li Bo; Yang Lijian; Geng Suxia; Weng Jianyu; Du Xin; Li Yangqiu (Journal of Hematology & Oncology, 2012)
Abstract A previous study has demonstrated a significant decrease in the TCRζ gene expression level in chronic myeloid leukemia (CML); thus, we further investigated the expression of TCRζ-regulating factors, the distribution of the TCRζ 3' untranslated region (3'-UTR) splice variants, and the expression level and correlation of the alternative splicing factor/splicing factor 2 (ASF/SF-2), FcεRIγ and ZAP-70 genes. TCRζ 3'-UTR splice variants were identified in peripheral blood mononuclear cells (PBMCs) from 14 healthy individuals, 40 patients with CML and 22 patients with CML in complete remission (CML-CR) by RT-PCR. The expression level of the TCRζ, FcεRIγ, ASF/SF-2 and ZAP-70 genes was analyzed by real-time quantitative PCR. While the expression of TCRζ gene in the CML group was significantly lower than that in the healthy individual and CML-CR groups, a significantly higher expression of the FceRIγ and ASF/SF-2 genes was found in the CML group. Two types of splicing forms were detected in all of the healthy individual CML-CR cases: wild type (WT) TCRζ 3'-UTR and alternatively splieced (AS) TCRζ 3'-UTR which have been alternatively splieced in the WT TCRζ 3'-UTR . However, 35% of the CML cases contained only the wild type TCRζ 3'-UTR isoform. Based on the TCRζ 3'-UTR isoform expression characteristic, we divided the patients with CML into two subgroups: the WT+AS- CML group, containing patients that express only the wild type TCRζ 3'-UTR, and the WT+AS+ CML group, which contained patients that expressed two TCRζ 3'-UTR isoforms. A significantly different ASF/SF-2 and FcεRIγ gene expression pattern was found between the WT+AS- and WT+AS+CML groups. We concluded that defective TCRζ expression may be characterized in the WT+AS-and WT+AS+CML subgroups by the different gene expression pattern. The overexpression of ASF/SF2, which alternatively splices the TCRζ 3’-UTR, is thought to participate in feedback regulation. The characteristics of TCRζ 3'-UTR alternative splicing may be a novel immunological marker for the evaluation of the CML immune status.